Organized by Klitsa Antoniou - Antoniou, Klitsa (My University, 2026)
Collaborative Art Project II Geert Vermeire: Walking Arts 2.0 Open Lecture: Walking Arts 2.0 Amphitheatre 1, Tassos Papadopoulos Building, Themis and Ifigenia corner 19 October 2021, 20:00 Workshop: Walking Arts 2.0 18-21 October 2021 Organized by Klitsa Antoniou